Associação da condição social e clínica à capacidade para alimentar crianças verticalmente expostas ao HIV - Bick, Marília Alessandra (2017)
Children vertically exposed to HIV demand care related to prophylaxis, follow-up in specialized service and food and nutrition, considering the national recommendation of non-breastfeeding. Breast milk is one of the most important interventions to reduce the risk of infant mortality. On the other hand, HIV positive women are advised against breastfeeding because of the possibility of HIV transmission. Recognizing that the child depends on the care provided by the family, a research was developed to evaluate the family's ability to feed them. A cross-sectional study, conducted with caregivers of infants exposed to HIV, with up to 18 months of age, followed up in a specialized service in southern Brazil. Data collection developed from February 2016 to March 2017, using a socioeconomic and demographic characterization tool for mothers and children, as well as the Capacity Assessment Scale for Children Exposed to HIV, composed of five dimensions of which were Used in II (preparing and administering milk feed) and III (complementary feeding). For data analysis, the variables were described by absolute and percentage distribution, and Pearson's chi-square test and Fisher's exact test were used for the association of these with capacity levels, at a significance level of 5%. Regarding the quality of the information available in the SINAN notification sheets and medical records, a greater occurrence of incompleteness of the data related to the child regarding the factors of prevention of vertical transmission was identified. Regarding the quality of the information available in the SINAN notification sheets and medical records, the greater occurrence of incompleteness of the data related to the child. Regarding the characterization of the social and clinical profile of infected pregnant women, data analysis shows the age range of young adults, low schooling and unpaid occupation. The majority of mothers performed prenatal follow-up (82.8%) with treatment adherence (80%), according to nationally recommended prophylactic measures. It was evidenced the high global capacity to feed (76.6%), for formula feeding (85.0%) and complementary feeding (65%). For the formula, the higher possibility of the caregiver to have high capacity: to access the basic unit (p=0.033), to present other children exposed to HIV (p=0.013), to maintain follow up at the health service (p=0.048) and don't drinking alcohol (p=0.045). Residing in the city outskirts zone (p=0.002) indicated moderate capacity. For the complementary feeding, the higher the schooling (p=0.025), the number of scheduled appointments for the child (p=0.045), the attendance at the health service (p=0.035) and access to the basic unit were related to high capacity. It is identified the commitment of the quality of health care directed to this population, mostly exposed to unfavorable conditions. The social and clinical factors of caregivers may have undue influence on the child. To ensure adequate nutrition in the case of HIV, it is necessary that the health services are able to consider the design of the guidelines as local, social and cultural realities in which as families are inserted.